Pengembangan Lembar Kerja Peserta Didik Terintegrasi Nilai Islam dengan Model Quantum Learning di Sekolah Dasar - Dahlianti, Revi; Faisal Ahmad (Lembaga Anotero Scientific Pekanbaru, 2025)
This study aims to produce Islamic-based student worksheets withmodelsstudent quantum learninglearning outcomes. to improvethe learning outcomes of students in grade IV Elementary School (SD) are valid and practical. This type of research is research and development (R&D) with the ADDIE model. This study used random sampling, namely for small group trials, a sample of 9 students was taken at SDN 020 Balung. The data collection technique is a LKPD validation questionnaire consisting of material experts, and education technology experts. Practicality questionnaire filled by students and teachers. The results of the assessment of the validity of the LKPD by the technology validator obtained an average of 85% with the criteria of